Marginal employment and health in Germany and the United Kingdom: Does unstable employment predict health? - Eunice Rodriguez (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
This study examines the possible health impact of marginal employment, including both temporary and part-time employment schemes. It addresses a growing concern in Europe that fixed-term employment and other forms of marginal employment may generate social inequality. Logistic regression models were used to analyze panel data from Germany and the U.K. (1991-93), available in the Household Panel Comparability Project data base. We included 11,980 respondents from Germany and 8,729 from the United Kingdom. The health dependent variable used was a single measure of perceived health status. – – In der Studie werden potentielle gesundheitliche Folgen prekärer Beschäftigungsverhältnisse einschließlich Zeitarbeit und Teilzeitbeschäftigung untersucht. Ausgangspunkt sind die wachsenden Befürchtungen in Europa, daß befristete Beschäftigungsverhältnisse und andere Formen prekärer Beschäftigung soziale Ungleichheit befördern könnten. Daten der Jahre 1991 bis 1993 des Household-Panel-Comparability-Projekts wurden mittels logistischer Regressionsmodelle für Deutschland (11.980 Personen) und Großbritannien (8.729 Personen) analysiert. Die Kategorie 'Gesundheit' wurde als einzige Variable des von den Befragten selbstwahrgenommenen Gesundheitszustands herangezogen.
Keywords: 330; Ungeschützte Beschäftigung; Befristeter Arbeitsvertrag; Gesundheit; Arbeitspsychologie; Schätzung; Deutschland; Großbritannien